Establishing H angle hard tissue and H angle soft tissue norms in skeletal class i Malay adult females and the correlation between the h angles and visual perception of laypersons - Cheong, Joo Ming; A. Halim, Nur Adlina; Mohammad, Norsyamimi; Sivagnanam, Mangaiyarkarasi; Mohd Ibrahim, Mohamad Shafiq (Thieme, 2024)
Objectives: This study aimed to establish the cephalometric norms of H angle soft tissue and hard tissue of Malaysian Malay adult females, and to evaluate the correlation between H angles and visual perception in skeletal Class I Malay adult females. Materials and Methods: 85 lateral cephalograms of skeletal Class I (mean ANB value = 3.15 ± 0.77) Malaysian Malay female patients aged 20–40 years (mean age = 28.6° ± 5.86°) taken from October 2017 to December 2021 were measured for H angle soft tissue and H angle hard tissue. 20 silhouettes were then converted from cephalometric films and were rated according to facial convexity/concavity by 20 laypersons, with re-evaluation after 2 weeks for intra- and inter-examiner reliability. Results: The means of the H angles soft tissue and hard tissue were 15.75° ± 4.16° and 11.64° ± 4.71° respectively. The intra-examiner reliability test for visual perception ranged from -0.89 to 0.99 indicating poor to excellent reliability, whereas the inter-examiner reliability test was 0.82 indicating good reliability. A highly statistically significant association between the H angles soft tissue and hard tissue (r=0.938; p<0.01) was found. There was no correlation between H angles and visual perception. Conclusions: The cephalometric norms of H angle hard and soft tissue in the Malaysian Malay female population were established: 11.64° (± 4.71°) and 15.75° (± 4.16°) respectively. There was a strong correlation between H angle soft tissue and H angle hard tissue amongst skeletal Class I Malay adult females. There was no correlation between H angles and the visual perception of laypersons.